The thin red line - Malick, Terrence 1945-; Weber, Billy; Jones, Leslie; Zimmer, Hans; Penn, Sean 1960-; Brody, Adrien; Caviezel, Jim 1968-; Chaplin, Ben; Clooney, George; Cusack, John 1966-; Harrelson, Woody; Koteas, Elias 1961-; et al.
In World War II, the outcome of the battle of Guadalcanal will strongly influence the Japanese's advance into the Pacific. The reasons for this war get further away as the world for the men gets smaller and smaller until their fighting is for mere survival and the life of the other men with them.